Predicting of Protein Requirement and Metabolizable Energy on Breast Percentage and Wing Percentages of Local Chickens: A Meta-Analysis - VM Ani Nurgiartiningsih; Osfar Sjofjan; Danung Nur Adli; Anisa Ramadhani (Faculty of Animal Science, Universitas Brawijaya, 2023)
This study aimed to assess the impact of dietary energy and protein balance on carcass weight and percentage during the initial growth phase of local chickens, utilizing a meta-analysis approach. The analysis involved integrating data from 11 articles comprising a total of 120 data points. These articles provided insights into the influence of energy and protein-balanced diets on breast and wing percentages in local chickens. The meta-analysis process involved data collection from diverse scientific publications, standardizing units, and tabulating the information in a Microsoft Excel database. Subsequently, SAS was employed to analyse the tabulated data. The findings revealed that a minimum breast percentage of 30.11% required 18.18% protein, and the associated metabolizable energy requirement was 2974.17 kcal/kg. In summary, achieving a minimum wing percentage of 14.19% necessitated 17.81% dietary proteins and 2943 kcal/kg metabolizable energy for a 14.08% wing percentage.